Chest Ultrasonography in Diagnosing Etiology of Acute Respiratory Failure - Pant, Chiranjibi; Pal, Anusmriti; yadav, Manoj; Shrestha, Bishow Kumar; Rana, Suraj (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Lung ultrasonography (LUS) is a useful diagnostic tool in critical care setting. Lung ultrasound at bed side is relatively easy to perform, cost effective and reproducible. Analysis of various sign and profile, alone or in combination is as accurate as gold standard test like Computed Tomography scan of the chest in detection of etiology of acute respiratory failure. The aim of our study was to perform bed side lung ultrasound in patent with ARF and to find out the diagnostic accuracy of lung ultrasound when compared with diagnosis made by the clinician.Methods: This descriptive observational study was conducted at tertiary care teaching centre in Nepal between February 2019 and July 2019. Consecutive samples of acute respiratory failure patient were included. Lung ultrasound was performed at bed side by fellows of pulmonary critical care medicine. Specific 10 signs of blue protocol were assessed in six different sites of both the chest. Findings of LUS was recorded and analysed to formulate a diagnosis, and finally compared with the final diagnosis.Results: Forty eight patients of acute respiratory failure with median age of 66 years (17 to 89 years) were included with 66.7% being females. 97.9 % of the patient presented with acute shortness of breath of less than one week duration. A total of 13 different diagnosis was made at the end of the treatment for all the patient. LUS accurately diagnosed them in 43 cases, with an overall accuracy of 89.6 %. Chronic obstructive pulmonary disease, pulmonary edema, pneumonia, pleural effusion, pneumothorax were accurately diagnosed with LUS however in acute respiratory distress syndrome and interstitial lung disease, lung ultrasound had poor diagnostic accuracy.Conclusions: Lung ultrasound is useful tool in diagnosing etiology of acute respiratory failure. Diagnosis made by lung ultrasound was 89.6% correct when compared with final diagnosis made by clinician.